A global tug of war: a topography of micro-business financing - Gullifer, L; Tirado, I (Duke University, 2018)
Micro-businesses are the lifeblood of any functioning economy: they are more numerous and, collectively, have a higher turnover than any other form of business in the majority of countries around the globe. In all parts of the world, developed and undeveloped, however, they are starved of finance, and the finance that is available is often on unsuitable and unsatisfactory terms. This paper maps out the reasons for this, as well as particular problems caused by the unique characteristics of micro-businesses, and suggests some legal and institutional responses. Some responses are designed to increase access to finance for micro-businesses, by proposing measures to eliminate barriers, decrease costs and increase lender certainty. Others, however, are suggested in order to protect the borrowers, as by their nature, micro-businesses are vulnerable to abuse of bargaining power, and, since many of the risk-takers are individuals, lack of protection leads to social problems. These two rationales for legal response are in direct tension with each other in that a legal response designed to achieve the former usually cuts across the aim of the latter and vice versa. Without an appropriate balance being reached, changes designed to facilitate the financing of micro-businesses can either end up being so oppressive that the very people the changes are designed to assist fail to thrive economically or socially, or go too far towards protecting the borrowers and fail to increase access to credit. The actual decisions as to the appropriate balance are, of course, a matter of policy and will vary from state to state, depending on many factors. This paper merely seeks to identify responses and the resulting tensions, and go some way towards mapping out a framework for achieving that appropriate balance.